Surviving and thriving: What do survivors of gynecologic cancer want? - Rayne Peerenboom; Sarah A. Ackroyd; Cecilia Chang; Elena Diaz Moore; Tilley Jenkins Vogel; Melissa H. Lippitt; Gustavo Rodriguez; Carolyn V. Kirschner (Elsevier, 2022)
The purpose of this study was to characterize survivorship concerns and survivorship program preferences among gynecologic cancer survivors. Women treated for gynecologic malignancy at our cancer center were surveyed from 1/2019 to 10/2020 on concerns and preferences using a 5-point Likert scale. Descriptive analysis and multivariable logistic regression were performed to describe survivors' concerns/preferences. The most frequent survivorship concerns were fear of cancer recurrence (49.6%), desire to lose weight (40.0%), and long-term side effects (30.7%). The highest ranked survivorship program components included assistance with nutrition (36.5%), weight loss (30.4%), and stress reduction (29.0%). Older patients (≥64 y) were less likely to report concern with losing weight (OR 0.26, p < 0.05), sex life (OR 0.18, p < 0.01), and strain in family relationships (OR 0.27, p < 0.05) compared with younger patients. Compared with ovarian/fallopian tube/primary peritoneal cancer survivors, endometrial cancer survivors were less likely to desire nutritional education (OR 0.06, p < 0.01). Participants with advanced cancer were less likely to desire assistance with weight loss than those with early stage cancer (OR 0.23, p < 0.05). A significant portion of gynecologic cancer survivors reported a fear of cancer recurrence. Assistance with nutrition and weight loss were the most desired survivorship program components. Variation in patient preferences and differences among clinical subgroups highlight the need for tailored survivorship care.